Enhancing Public Wellbeing Through Autogate at Soekarno-Hatta International Airports - Gunawan Ari Nursanto; Isidorus Anung Prabadhi; Besse Hartati; Wilonotmo Wilonotmo; Nurul Maharani Piranti (PT. Publikasiku Academic Solution, 2024)
The rapid advancement of information technology (IT), marked by innovations such as artificial intelligence (AI) is reshaping various sectors and challenging traditional frameworks, particularly towards automation. This transformation is particularly evident in public policy, as governments strive to enhance efficiency and citizen satisfaction. The adoption of information and communication technology, such as Autogate systems, emerges as a crucial strategy. In the context of immigration services, Autogate facilitates expedited immigration clearance procedures through biometric technology, enhancing security and efficiency. However, the implementation of such technologies raises concerns about public wellbeing. This research aims to assess the use and impact of Autogate technology on public wellbeing, focusing on its implementationat at Soekarno-Hatta Airport. The research methodology employed in this study involves two key approaches, interviews and observational studies. Findings reveal significant improvements in passenger experience and immigration efficiency, highlighting the potential of Autogate to enhance border management and public wellbeing. This research contributes to understanding the implications of technological advancements in immigration management and informs policymakers and stakeholders about the opportunities and challenges associated with Autogate implementation and public well being.